Lectures on Logic and Computation ESSLLI 2010 Copenhagen, Denmark, August 2010, ESSLLI 2011, Ljubljana, Slovenia, August 2011, Selected Lecture Notes - Bezhanishvili, Nick.; Goranko, Valentin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The European Summer School in Logic, Language and Information (ESSLLI) is organized every year by the Association for Logic, Language and Information (FoLLI) in different sites around Europe. The main focus of ESSLLI is on the interface between linguistics, logic and computation. ESSLLI offers foundational, introductory and advanced courses, as well as workshops, covering a wide variety of topics within the three areas of interest: Language and Computation, Language and Logic, and Logic and Computation. During two weeks, around 50 courses and 10 workshops are offered to the attendants, each of 1.5 hours per day during a five days week, with up to seven parallel sessions. ESSLLI also includes a student session (papers and posters by students only, 1.5 hour per day during the two weeks) and four evening lectures by senior scientists in the covered areas. The 6 course notes were carefully reviewed and selected. The papers are organized in topical sections on computational complexity, multi-agant systems, natural language processing, strategies in games and formal semantics.
Keywords: Computer science; Computer software; Logic design; Computational complexity; Artificial intelligence; Logic, Symbolic and mathematical; Computer Science; Logics and Meanings of Programs; Algorithm Analysis and Problem Complexity; Mathematical Logic and Formal Languages; Mathematical Logic and Foundations; Discrete Mathematics in Computer Science; Artificial Intelligence (incl. Robotics).